If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ln(lnx) + -1ln(5lnx + -6) = 0 Multiply ln * lnx 2l2n2x + -1ln(5lnx + -6) = 0 Reorder the terms: 2l2n2x + -1ln(-6 + 5lnx) = 0 2l2n2x + (-6 * -1ln + 5lnx * -1ln) = 0 2l2n2x + (6ln + -5l2n2x) = 0 Reorder the terms: 6ln + 2l2n2x + -5l2n2x = 0 Combine like terms: 2l2n2x + -5l2n2x = -3l2n2x 6ln + -3l2n2x = 0 Solving 6ln + -3l2n2x = 0 Solving for variable 'l'. Factor out the Greatest Common Factor (GCF), '3ln'. 3ln(2 + -1lnx) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(2 + -1lnx)' equal to zero and attempt to solve: Simplifying 2 + -1lnx = 0 Solving 2 + -1lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1lnx = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1lnx = 0 + -2 -1lnx = 0 + -2 Combine like terms: 0 + -2 = -2 -1lnx = -2 Divide each side by '-1nx'. l = 2n-1x-1 Simplifying l = 2n-1x-1Solution
l = {2n-1x-1}
| a-6.6=10.1 | | -17x+2(x+14)=-2 | | y^2=x^2-x^4 | | (X^8)-1=0 | | R+4=12 | | 6n+45=4n-15 | | f(x+4)=8(x+4)-2 | | (8+z)(5z+9)=0 | | -2-3x+5=16+2x+22 | | .75x=.51 | | 8.5x-12=6.5x-18 | | (4z+5)(4+z)=0 | | 27y^3+36y^2+12y= | | y=6x^2+7x-10 | | 8.5x-12=6.5-18 | | 6-2x+8y+4x-15y= | | 1-t+2.2t=5.9 | | m^2+10m+41=0 | | 0.5(x+6)+1.5(x-5)= | | z^2-20=0 | | 3(1+h)=3h-9 | | 7y^2+12y=0 | | .8x=43 | | 3s^3-16s+5= | | 2x^2+4x+5=x | | -6y^2+53y+9= | | -.22x=.4 | | 32.31+31.32x=41.89 | | 2log^3x=log^3(x+6) | | 1.25x=3.75 | | 2xsquared+8=0 | | -10x^2+79x+8= |